Carotidynia: A Rare Diagnosis for Unilateral Neck Pain Revealed by Cross-Sectional Imaging - Corrado Santarosa; Salvatore Stefanelli; Roman Sztajzel; Pravin Mundada; Minerva Becker (Case Reports in Radiology)
Idiopathic carotidynia (IC) is a rare and poorly understood syndrome consisting of unilateral neck pain, tenderness, and increased pulsations over the affected carotid bifurcation. A growing body of evidence supports the hypothesis that IC is a distinct clinicopathologic entity with characteristic imaging features. We report the case of a 34-year-old Caucasian male presenting with intense unilateral neck pain in the emergency setting. Computed tomography and ultrasonography revealed fusiform eccentric thickening of the ipsilateral carotid bifurcation without vessel narrowing. Contrast-enhanced magnetic resonance imaging depicted major perivascular enhancement without evidence of dissection. Further imaging and laboratory work-up excluded vasculitis. The diagnosis of IC was made. The patient was treated with nonsteroidal anti-inflammatory drugs and symptoms and imaging findings disappeared within a few weeks. Cross-sectional imaging allows not only ruling out IC mimickers but also making the correct diagnosis of this rare condition, in particular, as the clinical presentation of IC is often nonspecific.